WORK ENGAGEMENT KARYAWAN GENERASI MILENIAL DITINJAU DARI JOB CRAFTING DAN JOB DEMANDS - Rabbani, Alifu Dzikri (Universitas Gunadarma, 2024)
The phenomenon of the dominance of the millennial generation in the world of work, coupled with the phenomenon of relatively low work engagement of millennial generation employees, is a challenge for companies to not only retain talented individuals but also find individuals who are engaged with the company. The purpose of this study is to determine whether job crafting and job demands have an influence on the work engagement of millennial generation employees. This study was conducted on 98 millennial generation employees using the utrech work engagement scale, job crafting scale and job demands scale. The sampling technique used was purposive sampling. Hypothesis testing with linear regression techniques. The results of this study indicate that the hypothesis of this study is accepted with the influence of job crafting variables on work engagement has a sig value. 0.000 and the value of t count 7.647 which means the influence of job crafting on work engagement. The value of the influence of job demands variable on work engagement has a sig value. 0.040 and t count 2.080 which means the influence of job demands on work engagement. The value of the influence of job crafting variables and job demands on work engagement has a sig. 0.000 and f count 87.045. These results indicate that job crafting and job demands simultaneously affect the work engagement of millennial generation employees.